Economic Assessment of Damage Caused by Drought - Panaitescu, Manuela; Andronic, Bogdan; Chiru, Gheorghe (Acta Universitatis Danubius. Œconomica, 2022)
High temperatures and prolonged drought have caused farmers, households and agricultural production across Europe to face unprecedented damage in the period 2019-2021. Drought is a natural feature of climate variability and water cycle and can occur in all climatic zones. It comes from a temporary reduction in the normal rainfall regime over an extended area, but other climatic factors, such as high temperatures and winds or low relative humidity, can significantly worsen the severity of the event. The loss and damage caused by the weather in the agricultural sector will lead to a decrease in global agricultural production, causing food insecurity. the consequences for the export of food and agricultural products.